(untitled) (Research, Society and Development, 2025)
The knee is an extremely important joint, assisting us in walking and standing, and one of its main components, the anterior cruciate ligament, functions to stabilize it, making it vital for the professional life of an athlete, especially soccer players, and a well-strengthened knee prevents subsequent injuries. The objective of this study was to present the advantages of kinesiotherapy in patients undergoing ligamentoplasty of the anterior cruciate ligament, highlighting the benefits of different physiotherapeutic approaches in the rehabilitation process and in the promotion of individualized functional recovery. The methodology consists of an integrative literature review, including articles published between 2020 and 2025, selected based on scientific data, which address techniques such as dated kinetic chain exercises, hydrotherapy and electrical stimulation. The results indicate that early and individualized interventions promote significantly better muscular strength, amplitude of movement, balance and knee functionality, while also reducing the risk of post-surgical complications. It is concluded that structured physiotherapy treatment is essential to optimize post-operative recovery, guaranteeing greater safety, autonomy and quality of life for patients, especially athletes and individuals with a high functional level.